2020
DOI: 10.1177/0361198120934476
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Lateral Interactions of Motorized Two-Wheelers using Multi-Gene Symbolic Genetic Programming

Abstract: Complex maneuvering patterns are typical of motorized two-wheelers (MTWs), and their widespread adoption in many countries has spurred a growing response from transport researchers to model their dynamic behavior realistically. Considering the increased vulnerability of MTW drivers in dense urban mixed traffic systems, proper evaluation and modeling of lateral interactions between the drivers/riders moving abreast need to be addressed. A proper investigation can essentially help in understanding the behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…But the values in these studies are obtained from optimizing the macroscopic parameters of travel time or delay. It is well articulated that different variables or driving behavior representative parameters (DBRPs)-such as relative speed, spacing, acceleration of various vehicles under different conditions, space headways, lateral shift, and lane changes-form key inputs to different driving behavior models, especially for disordered traffic conditions (3,16,24). Therefore, the values of different DBRPs would govern these models' efficacy in modeling traffic behavior.…”
Section: Research Motivationmentioning
confidence: 99%
“…But the values in these studies are obtained from optimizing the macroscopic parameters of travel time or delay. It is well articulated that different variables or driving behavior representative parameters (DBRPs)-such as relative speed, spacing, acceleration of various vehicles under different conditions, space headways, lateral shift, and lane changes-form key inputs to different driving behavior models, especially for disordered traffic conditions (3,16,24). Therefore, the values of different DBRPs would govern these models' efficacy in modeling traffic behavior.…”
Section: Research Motivationmentioning
confidence: 99%
“…They applied the Boruta algorithm to select potential features in the developed model, where only traffic-related features were considered and not the effect of the surrounding traffic environment. In contrast, recent studies by Das et al ( 15 ) and Das and Maurya ( 11 ) indicated the importance of considering the presence of leading and adjacent vehicles in estimating lateral clearance of MTWs while riding abreast. Besides, the execution of lateral shift is a process that depends on the number of attempts made by the rider to make a successful lateral shift, which indeed plays a significant role in understanding the behavioral intentions of a rider to make a shift and his/her driving style during the process.…”
mentioning
confidence: 90%
“…Besides, the execution of lateral shift is a process that depends on the number of attempts made by the rider to make a successful lateral shift, which indeed plays a significant role in understanding the behavioral intentions of a rider to make a shift and his/her driving style during the process. Furthermore, with respect to methodological approaches, the binary logit model was one of the major modeling preferences adopted in several studies related to filtering and overtaking maneuvers of MTWs ( 8 , 11 , 15 ). However, some advanced models, such as multiple indicators–multiple causes (MIMIC) latent variable models ( 9 ), the decision tree ( 10 ), and the multigene genetic programming algorithm, were also applied to evaluate MTWs’ lateral interaction behaviors.…”
mentioning
confidence: 99%
“…The driving behavior studies [2,3] from mixed traffic demonstrates smaller vehicles' lateral behavior impacting mixed traffic performance. Simultaneously, given the variation in the vehicles' physical properties, earlier studies [4,5] reported the underperformance of automated traffic tools in monitoring mixed traffic conditions. Due to the mixed traffic data constraints, the driving behavior studies from mixed traffic have not taken proper shape.…”
Section: Introductionmentioning
confidence: 99%